In vitro Culture of Immature Embryos of Mastic Tree (Pistacia lentiscus L.) - Mohammad Mahmoudi Meymand; Barbara Ruffoni; Carlo Mascarello; Marco Savona; Mohammad Shamshiri; Khalil Malekzadeh (Journal of Nuts, 2022)
Immature lentisk (Pistacia lentiscus L.) seeds from plants grown in Liguria (Italy) were collected and surface sterilized with ethanol (70%) and then NaOCl (1%). The outer pericarp of the immature fruits was removed and shells were opened. Enhancement of Embryo germination was examined through the use of five sucrose concentrations (0, 15, 30, 45, and 60 g L-1) combined with five concentrations of GA3 (0, 0.1, 0.3, 0.5, and 0.7 mg L-1). After 14 days, the germination frequency was detected and after 16 days, seedling development was evaluated. The embryo development into plantlets increased up to 54.37% when 45 g L-1 of sucrose was supplied; at this concentration, all the parameters, such as plantlet weight, height, and root length were high, while at 60 g L-1 of sucrose, the plantlets showed many lateral root formations. The root shape was completely different among the treatments. The percentage of embryo germination, plantlet weight and height, root length, and main lateral root number were enhanced when GA3 was used in the concentration of 0.7 (mg L-1). No rooting at all was observed when GA3 was used in a concentration of 0.3 or 0.5 (mg L-1) or medium without GA3. This research increases the possibility to obtain a massive number of plants to be used as rootstock for pistachio cultivation in difficult soils.